Made in Canada! The Canadian Manufacturers’ Association’s Promotion of Canadian-Made Goods, 1911-1921 - Siegel, Andre; Hull, James (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2014)
Beginning just before WW1 and continuing into the postwar period, the Canadian Manufacturers’ Association mounted a campaign to sell Canadian consumers on the virtues of buying “Made in Canada” goods. Not simply an appeal to patriotism, this campaign had to convince Canadian consumers of the satisfactory quality of such goods — which manufacturers had to deliver the substance of — in an increasingly sophisticated retail and marketing environment. Such an encouragement of the demand side of the producer/consumer equation is an important example of the proactive stance taken by Canadian manufacturers in the early twentieth century to improve their own viability and success. This paper examines the “Made in Canada” campaign as part of a range of business strategies that also included support for scientific industrial research, technical standardization, and vocational education, alongside more traditional anti-competitive policies. The scope of these strategies suggests that the impact of the Second Industrial Revolution was being fully felt in Canada and business leaders recognized the implications of a new political economy in which an unimaginative defence of the protective tariff was no longer adequate.